Expert-opinion-based guidance for the care of children with lysosomal storage diseases during the COVID-19 pandemic: An experience-based Turkey perspective - Akgun, Abdurrahman; Gokcay, Gulden; Mungan, Neslihan Onenli; Sivri, Hatice Serap; Tezer, Hasan; Zeybek, Cigdem Aktuglu; Ezgu, Fatih (Frontiers Media Sa, 2023)
This expert-opinion-based document was prepared by a group of specialists in pediatric inherited metabolic diseases and infectious diseases including administrative board members of Turkish Society for Pediatric Nutrition and Metabolism to provide guidance for the care of children with lysosomal storage disorders (LSDs) during the COVID-19 pandemic in Turkey. The experts reached consensus on key areas of focus regarding COVID-19-based risk status in relation to intersecting immune-inflammatory mechanisms and disease patterns in children with LSDs, diagnostic virus testing, particularly preventive measures and priorities during the pandemic, routine screening and diagnostic interventions for LSDs, psychological and socioeconomic impact of confinement measures and quarantines and optimal practice patterns in managing LSDs and/or COVID-19. The participating experts agreed on the intersecting characteristics of immune-inflammatory mechanisms, end-organ damage and prognostic biomarkers in LSD and COVID-19 populations, emphasizing the likelihood of enhanced clinical care when their interaction is clarified via further studies addressing certain aspects related to immunity, lysosomal dysfunction and disease pathogenesis. In the context of the current global COVID-19 pandemic, this expert-opinion-based document provides guidance for the care of children with LSDs during the COVID-19 pandemic based on the recent experience in Turkey.
Keywords: lysosomal storage diseases; COVID-19 pandemic; specialized care; expert opinion; immune-inflammatory mechanisms